Technology-Enhanced Project-Based Learning: The Role of Wordwall in Reading Comprehension classes - Amalia, Diva Sifatul; Herawati, Siane; Liskinasih, Ayu (Journal of English Language and Education, 2025)
Reading comprehension is a basic skill plays an important role in students' academic success and overall language proficiency. This study aims to find out the effect of using technology Wordwall media on supported PjBL strategy on students' reading comprehension. This study is a quantitative research used a quasi-experimental design. The data obtained has been analyzed using SPSS version 25, including descriptive statistics, normality, homogeneity and an independent sample t-test. The results of this study showed that PjBL assisted by Wordwall significantly had a positive impact on students' reading comprehension skills. The sig (2-tailed) shows the result is 0.00 which is smaller than 0.05 (α .05 ). The results of the pre-test and post-test comparisons of the control group show that PjBL and Wordwall influence reading comprehension. The experimental group obtained an average pre-test score of 57.50 and a post-test score of 80.00, which means an increase of 22.50 points.